Bimbingan Menghafal Alquran Menggunakan Metode Wahdah, Kitabah, dan Sima’i di Rumah Tahfiz Baitul Qur’an Desa Durian Kecamatan Sambas - Al Azhar; Henny Yusnita; Enik Sartika (Jurnal Ilmiah Al-Muttaqin, 2025)
Memorizing the Qur’an is not an easy task; in other words, it is not as simple as turning one’s palm. One important effort that must be considered in guiding Qur’an memorization is the method used. This study aims to explain the guidance for memorizing the Qur’an using the wahdah, kitabah, and sima’i methods at the Baitul Qur’an Tahfiz House in Durian Village, Sambas District. This research employs field research with a descriptive approach. Data sources were obtained from ustaz (teachers/mentors), students (santri), and the administrators of the Baitul Qur’an Tahfiz House. Data collection techniques included: (1) non-participant observation, (2) structured interviews, and (3) documentation. The data analysis techniques used consisted of data reduction, data display, verification, and drawing conclusions. Data validity was examined using source triangulation and member checking. The results of the study successfully revealed the methods used in guiding Qur’an memorization as follows: (1) The wahdah method has been implemented in the guidance process, in which students read one verse of the Qur’an repeatedly under the guidance of an ustaz until they are fluent in terms of pronunciation, tajwid, and makharij al-huruf. After the first verse is mastered well, students proceed to the next verse. Subsequently, the first and second verses are repeated together until the memorization is correctly connected. This process is carried out continuously until several verses or one page can be memorized fluently; (2) The kitabah method involves teaching students to write the verses of the Qur’an, and as a subsequent program, students who enjoy writing Arabic (hijaiyah) letters are directed toward the art of Arabic calligraphy; (3) The sima’i method also trains students’ listening skills by having them listen to Qur’anic verses either orally or through audio-visual media. This method also facilitates memorization, as students continuously listen to the recitations played through audio or audio-visual media.